"The ultimate small business guide to getting more local business from the Internet" within the next 30 days - Edwards, Jim; MMIX Guaranteed Response marketing ([Lightfoot, VA] : MMIX Guaranteed Response marketing, 2009)
Discover how any small business can quickly and easily get more local business from the internet, create a loyal following, and get customers coming back again and again
disc. 1. Sales copywriting crash course: how to quickly write headlines, bullets and offers that sell like crazy! ; disc. 2. Local search secrets: how to show up on the first page of Google and more! ; disc. 3. Local Email list building: how to explode your business through the power of Email marketing.. ; disc. 4. Local Website traffic: 17 specific ways to get new customer traffic from the Internet
Title from container
DVD format
Keywords: Business -- Computer network resources; Business enterprises -- Communication systems